Rattlesnakes - Ethan, Eric. (Milwaukee, WI : Gareth Stevens Pub., 1995)
Describes what rattlesnakes look like, what they eat, where they can be found, how they defend themselves, the danger from their bites, and the outlook for their future.
Includes index.
Keywords: Rattlesnakes -- Fiction; Rattlesnakes; Poisonous snakes; Snakes